Abdominal Stretching Exercise Berpengaruh Terhadap Intensitas Dysmenorrhea Pada Remaja Putri - Ummah, Wiqodatul; Utami, Woro Tri (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
The signs of adolescence include physical changes driven by hormonal shifts. Among the complaints experienced by adolescent girls during menstruation is dysmenorrhea, often caused by a progesterone hormone imbalance. This hormonal imbalance triggers uterine contractions and stimulates pain responses in adolescent girls, especially at the onset of menstruation. Abdominal Stretching Exercise is a non-pharmacological therapy that can alleviate dysmenorrhea. The research aimed to determine the impact of Abdominal Stretching Exercise on the intensity of dysmenorrhea among adolescent girls at the Nurul Barokah Al-Islami Islamic Boarding School in Buring Kedungkandang, Malang City. The study utilized an experimental approach with a one-group pre-post-test design. The intervention occurred during menstruation from the first to the third day, with a daily duration of 20 minutes. The research population comprised 32 adolescent girls experiencing primary dysmenorrhea. The sample included 32 adolescent girls selected through total sampling. Data collection utilized the Faces Pain Scale-Revised (FPS-R) for pain assessment. Data analysis was performed using the Paired Sample t-test. The research results showed a p-value of 0.000 (α 0.05), indicating that Abdominal Stretching Exercise had an impact on the intensity of dysmenorrhea among adolescent girls at the Nurul Barokah Al-Islami Islamic Boarding School in Buring Kedungkandang, Malang City. The application of Abdominal Stretching Exercise proved effective in reducing the intensity of dysmenorrhea in adolescent girls. This therapy can serve as an alternative option to alleviate dysmenorrhea symptoms.